(untitled) (Ibrahim Medical College Journal, 2009)
To identify the main causes of neonatal morbidity and mortality a retrospective study was carried out at the Special Care Baby Unit (SCABU) of the Department of Paediatrics, Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) for a period of 1 year from January to December 2005. A total of 361 neonates were included in this cohort. The ratio of male (200) and female (154) neonates was 1:0.7. Most of the babies (300) were born in this hospital. Major causes of morbidity were prematurity (60.7%), LBW ( 48.2%), jaundice (23.3%), severe perinatal asphyxia (10.8%), transient tachypnoea of newborn (10.8%), respiratory distress syndrome (6.4%) and sepsis (6.4%). Most deaths were associated with prematurity (71.1%), LBW (65.8%), intrauterine growth retardation (23.7%), respiratory distress syndrome (36.8%), severe perinatal asphyxia (18.4%) and sepsis/pneumonia (15.9%). Outcome of babies born in this hospital was better than those referred from other hospitals (p < 0.001). Ibrahim Med. Coll. J. 2007; 1(2): 1-4 Key Words: Neonates, morbidity, mortality, baby care. doi: 10.3329/imcj.v1i2.2896